Проблеми визначення методик для оцінки фінансового стану підприємств - Ларка, Микола Іванович; Золотарьова, Аліна Русланівна (НТУ "ХПІ", 2016)
Основою стабільного положення підприємства і умовою його життєдіяльності в ринкових умовах виступає фінансова стійкість. Тому постає актуальність питань, що обумовлені недостатністю теоретичних та методичних розробок забезпечення фінансової стійкості підприємства, за допомогою яких можна визначити, які саме методи антикризового управління будуть потрібні конкретному підприємству. В статті розглянуті найпоширеніші методики оцінки фінансового стану підприємств та критеріїв, за якими виконується така оцінка. Обґрунтовано потребу їх системної класифікації, яка надасть можливість об’єднати різноманітні методичні підходи для отримання адекватної оцінки фінансового стану підприємства.

The basis of stability of the enterprise and the condition of its life financial stability stands in market conditions. Therefore there is a relevance of the issues caused by lack of theoretical and methodological approaches to ensure the financial stability of the company, with which you can determine what kind of crisis management techniques will need a particular enterprise. The urgency of this problem has led to the need to develop diagnostic methods of financial stability. It should allow financial analysіs and management personnel to form an idea of the system of management of efficiency of economic activities of enterprises, domestic economic growth opportunities, a way out of the crisis, and the like. The article describes the most common methods of assessing the financial situation of enterprises and the criteria by which such an assessment is carried out. The necessity of a system of classification, which will bring together a variety of methodological approaches to obtain an accurate assessment of the financial condition of the company.
Problems of definition of methodologies for assessing the financial condition of enterprises
Keywords: критерії; методика; фінансова стійкість; коефіцієнти; criteria; methods; financial stability